Exploring the effect of nanoholes on arsenene: a density functional theory study. (18th April 2018) - Mushtaq, M; Zhou, Y G; Xiang, X
Abstract: Effectively modulating the electronic and magnetic properties of a two-dimensional system is critical for the application of it in nanoscale devices. In this work, we explore the effect of nanohole on arsenene on the basis of density functional theory calculations. Our calculations show that, except slight distortion at the corner of nanoholes, geometries of both un-hydrogenated nanohole-embedded arsenene (As-NH) structure and hydrogenated nanohole-embedded arsenene (H-As-NH) structure are well maintained after optimization. Interestingly, the As-NH structure can be magnetized so that it can represent ferromagnetic, ferrimagnetic or antiferromagnetic behavior depending on the shape of the nanoholes. Furthermore, As-NH structure with triangle nanoholes is expected to exhibit remarkable magnetism. Besides, owning to the induction of flat defect levels by the nanoholes, As-NH structure can represent a relatively small band gap. In contrast, the H-As-NH structure is shown to lack the magnetism due to the saturation of unpaired As atoms. In this case, the H-As-NH structure exhibits a relatively large band gap due to the quantum confinement effect. These results indicate an opportunity for the design of arsenene-based nanoscale devices with potential applications in spintronic and optical fields.